2012
DOI: 10.1186/1472-6947-12-128
|View full text |Cite
|
Sign up to set email alerts
|

A study of diverse clinical decision support rule authoring environments and requirements for integration

Abstract: BackgroundEfficient rule authoring tools are critical to allow clinical Knowledge Engineers (KEs), Software Engineers (SEs), and Subject Matter Experts (SMEs) to convert medical knowledge into machine executable clinical decision support rules. The goal of this analysis was to identify the critical success factors and challenges of a fully functioning Rule Authoring Environment (RAE) in order to define requirements for a scalable, comprehensive tool to manage enterprise level rules.MethodsThe authors evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…CDSS rule management and maintenance have been recognised as challenging in large institutions,4 17–19 which usually have in-house technical support and adequate resources. Thus, we anticipate that CDSS rule management and maintenance will be one of the greatest challenges to increased use in office-based settings, especially in solo practices.…”
Section: Discussionmentioning
confidence: 99%
“…CDSS rule management and maintenance have been recognised as challenging in large institutions,4 17–19 which usually have in-house technical support and adequate resources. Thus, we anticipate that CDSS rule management and maintenance will be one of the greatest challenges to increased use in office-based settings, especially in solo practices.…”
Section: Discussionmentioning
confidence: 99%
“…Referring to the CIG authoring approach proposed by Zhou et al [ 26 ], we designed a rapid CIG development approach that parallelizes data modeling and rule editing. In addition to the original approach, the output of each step was specified to eliminate ambiguities between different participants.…”
Section: Methodsmentioning
confidence: 99%
“…Zhou et al [ 26 ] reported a CIG authoring approach with six steps, including (1) create a knowledge specification, (2) integrate with terminology, (3) author rules, (4) test rules, (5) publish rules, and (6) generate reports. These six steps should be carried out sequentially, and key artifacts are produced in each step.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in the particular case of guideline-oriented CDS that is based on rules, a recent study shows the lack of rule languages that allow for shareable and standardised rules in healthcare [ 11 ]. As the computerisation of guidelines often involves their representation as rules, that finding calls for health information systems that are based on standards, both when it comes to their EHRs and CDS components.…”
Section: Introductionmentioning
confidence: 99%